Three new Prothemenops species (Araneae: Idiopidae) from central Thailand - Schwendinger, Peter J.; Hongpadharakiree, Komson (Zootaxa, 2014)
Prothemenops irineae sp. n., P. khirikhan sp. n. and P. phanthurat sp. n. are described from males and females collected in the Thai provinces of Prachuap Khiri Khan and Phetchaburi. The diagnosis of the genus Prothemenops is emended to include these three species and others to be described later. Notes on variation of morphological characters, biology and phenology are given.